Effectiveness of The Combination Gym Ball and Peanut Ball Techniques on The Duration of Active Phase I Labor in Primigravida - Mella Yuria Rachma Anandita; Legina Anggraeni; Annisa K (JURNAL KEBIDANAN, 2023)
Prolonged parturition is one of the causes of increased mortality and morbidity in the mother and fetus. Mothers with prolonged labor have a higher risk of bleeding due to uterine atony, tearing of the birth canal, infection, shock and fatigue, while the fetus has an increased risk of cerebral trauma, severe asphyxia, infection and injury. Several physiological efforts that can be made to prevent prolonged labor include pregnancy exercise, breathing techniques and birthing ball techniques (Gym ball and Peanut Ball). The gym ball and peanut ball help the baby's head rotate to the optimal position during the first stage of labour. The aim of the research was to determine the effectiveness of the gym ball and peanut ball technique on the length of labor in the first stage of the active primigravida phase. The research method used the Quasy Experiment method with the Nonequivalent Control Group Design. The population of this study were mothers giving birth in Depok City, a sample of 105 primigravida mothers who were divided into experimental and control groups. The sample technique uses purposive sampling. The statistical test used is the two mean dependent difference test or the dependent T test (paired T test). The results of the study showed that the average difference in length of labor during the first stage of the active phase in primigravida using the gym ball and peanut ball technique lasted 3 hours 39 minutes. The results of the hypothesis test obtained a p value of 0.0001, which means that there is a difference in the average length of labor between the experimental group and the control group. The conclusion is that the gym ball and peanut ball techniques are effective in reducing the duration of the first stage of labor in primigravida.